Analysis Of Students’ Interest In Gresik City In Using Digital Investment - Zaidan Abdillah Alifianto; Dhani Ichsanuddin Nur (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
This study aims to analyze the interest of students in Gresik City in using digital investment, particularlycryptocurrency, as an alternative investment instrument. The research employs a quantitative approachwith data collected through questionnaires distributed to students in Gresik City. The sampling methodused was purposive sampling, with a total of 100 respondents. Data analysis was carried out usingmultiple linear regression with the help of SPSS software. The results show that Social Influence andFacilitating Conditions have a positive and significant effect on students’ interest in cryptocurrencyinvestment. Meanwhile, Performance Expectancy and Effort Expectancy do not have a significant effect.Simultaneously, the four independent variables significantly influence students’ investment interest.These findings indicate that social encouragement and the availability of supporting facilities are themain factors driving students to invest in cryptocurrency, while perceived benefits and ease of use arenot considered decisive factors.